Fatores associados à saúde mental de profissionais de um hospital público em tempos de pandemia de COVID-19: uma abordagem com vídeo animado e questionário estruturado interativo - Bogado, Amália Christina Brito Costa (2023)
More than 100 years have passed since the last Spanish flu pandemic in 1918, and the pandemic caused by the Coronavirus Disease - 19 (COVID-19) is an unprecedented event for the current world population. For this reason, it is natural that there is a scarcity of literature that deals with the mental health of Brazilian professionals who work in the care of patients with this diagnosis. Epidemiological surveys carried out through questionnaires applied directly by an interviewer, in the field of psychiatry, can often interfere with the answers given by the interviewees, especially in questions that involve particular matters that one does not wish to disclose. In this way, the use of self-administered questionnaires can leave the interviewee in a situation where they feel more secure and confident to provide intimate answers. The use of the video as a support tool before the application of the questionnaire attracted the attention of the participants, guides on the free and informed consent form and instructs on the completion of the questionnaire, in addition to providing important information about mental health. The aim of this study was to create an informative video, a self-administered and structured questionnaire in a Microsoft (MS) Access file and to assess whether factors (socioeconomic, occupational characteristics and past history) are associated with mental health (anxiety, depression, distress and insomnia) of health professionals who worked in the direct and indirect care of patients with COVID-19 during the pandemic. The questionnaire, structured and self-administered, has conditional controls programmed in Visual Basic, making it possible to navigate through the questionnaire, save responses, confirm consent for the stage before proceeding, record the time of participation and visualization by the participants of the scale results, based on their symptoms, immediately after the end of each scale application. The video and the questionnaire helped the development of a cross-sectional study, carried out with healthcare workers who care for suspected/infected patients with COVID-19, at a University Hospital in the Northwest of Paraná, Brazil. The independent variables were used: socioeconomic and occupational characteristics and previous history, which were associated with the dependent variables involving anxiety, depression, insomnia and distress. The association between the dependent and independent variables was verified using the chi-square or Fisher's exact test, considering a significance level of 5%, followed by multivariate analysis by binary logistic regression to establish the risk factors. All statistical analyzes were performed using the Statistical Package for Social Sciences (SPSS), version 20.0 (IBM Corp, NY, United States). It is concluded that, in the COVID-19 pandemic, healthcare in the COVID-19 sector have high rates of depression, anxiety, insomnia and distress, considering levels from mild to severe. Among the main findings, eleven predictive factors stood out, being age between 20 and 43 years, not having a degree, drug use by family members, mental illness in family members, history of psychiatric care, abuse in childhood and adolescence, having a relationship regular family, working in the ward, working for more than 7 months in the COVID-19 sector, with more than 60 hours per week and having the perception of being stigmatized by other people were predictors of symptoms of depression, anxiety, insomnia and distress. Both the video and the questionnaire served the purpose for which they were conceived.